1993
DOI: 10.1254/jjp.62.315
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of Blood Pressure and Heart Rate Control in Suncus

Abstract: ABSTRACT-Theanti-ischemic heart effect of (±)-(E)-4-ethyl-2-[(E)-hydroxyimino]-5-nitro-3-hexenamide (FK409), a novel nitric oxide donor, was studied in dog and rat preparations in vivo and in vitro. In anesthetized dogs with partially occluded coronary artery that were subjected to atrial pacing at a constant blood pressure, FK409 (1-100 pg/kg, i.v.) suppressed the ST-segment elevation on epicardial electrocar diograms. Glyceryl trinitrate (GTN; 10, 32 pig/kg) or dipyridamole (1000 ,ug/kg) failed to suppress t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It is relatively unstable, with a half‐life of approximately 45 min at 37°C in phosphate buffer. FK409 has been reported to attenuate experimental liver, cardiac, lung, and renal I/R injury14–17. We have recently shown that FK409 can improve survival and reduce microcirculatory disturbances after intestinal I/R injury18.…”
Section: Introductionmentioning
confidence: 97%
“…It is relatively unstable, with a half‐life of approximately 45 min at 37°C in phosphate buffer. FK409 has been reported to attenuate experimental liver, cardiac, lung, and renal I/R injury14–17. We have recently shown that FK409 can improve survival and reduce microcirculatory disturbances after intestinal I/R injury18.…”
Section: Introductionmentioning
confidence: 97%
“…Isono et al [15] extended this work by evaluating FK409 on coronary ischemia using the canine open chest, occluded coronary artery model. When the heart rate was increased by pacing for 5 minutes the electrocardiogram (ECG) showed an ST elevation which was more potently inhibited by FK409 (10 ug/kg, i.v.)…”
Section: ) Pharmacology Of Fk409mentioning
confidence: 99%
“…M . OHTSUKA ET AL.. 5 (16). It has been reported that GTN acts preferentially on the large canine coronary arteries in in vitro, this effect may contribute to the antianginal effect of the drug (36).…”
Section: Fk409mentioning
confidence: 99%
“…From the in vitro findings that FK409 acts preferentially on the large coronary artery (16,29,35), the compound may be expected to facilitate redistribution of the blood to the ischemic region of the myocardium due to dilation of the large conductive coronary or collateral vessels.…”
Section: Cardiovascular Effects In Vivomentioning
confidence: 99%
See 1 more Smart Citation